Effectiveness of Islamic Cognitive-Behavioral Counseling in Reducing Academic Burnout: A Mixed-Methods Study - Frendi Fernando; Kartika Wanojaleni; Fitroh Qudsiyyah; Trimulat Trimulat; Taqiyudin Subki (IJoIS: Indonesian Journal of Islamic Studies, 2026)
This study evaluates the effectiveness of Islamic Cognitive-Behavioral Counseling (ICBC) in mitigating academic burnout among university students. Employing an explanatory sequential mixed-methods design, the research involved 40 students with high burnout levels as measured by the Maslach Burnout Inventory-Student Survey (MBI-SS). Quantitative results revealed a statistically significant reduction in burnout scores, with the mean shifting from 68.51 to 44.87 (p < 0.001). The intervention yielded a massive effect size (Cohen’s d = 4.94), underscoring that the ICBC formulation is both robust and practically meaningful for student recovery. Qualitatively, the findings identified a Triple-Axis Transformation driving the change: neutralizing cynicism through the Tawakal-Control axis, reversing emotional exhaustion via Dhikr-based biological resets, and restoring personal accomplishment through Muhasabah-Amanah integration. The discussion highlights that by integrating spiritual tenets—specifically the Dichotomy of Control between Ikhtiar (effort) and Tawakal (divine reliance) the ICBC model provides a transcendental anchor that recalibrates students' stress appraisal more effectively than purely secular interventions. This spiritual strategy transforms academic tasks from burdensome chores into a form of Amanah (Divine Trust), moving students from fragile self-regulation to a higher-order ethical accountability. The study concludes that the ICBC model offers a culturally resonant and clinically robust solution that fills the existential gap found in conventional counseling, providing a more resilient motivational foundation for students navigating the pressures of modern higher education.